Visceral Pseudoaneurysms and the Role of Endovascular Treatment – a Case Report - Figueiredo, A (2021)
Introduction: Visceral pseudoaneurysms are pathological dilations of the visceral arteries and/or their branches. They are a rare entity but with devastating consequences given their high potential for rupture and hemorrhage. The evolution of endovascular techniques has changed the paradigm in the treatment of this entity, making it the preferred option for the elective treatment of visceral pseudoaneurysms. Clinical case: The authors described the case of a pancreatic pseudoaneurysm in a young male patient, with past medical history of chronic pancreatitis and pancreatic pseudocyst, marked smoking and alcoholic habits, which presented with an abdominal pain and a drop in hemoglobin. After discussing the case with the Vascular Surgery department, it was decided towards an endovascular treatment given the patient's clinical stability and appropriate anatomical location for the proposed intervention. Coil embolization via humeral artery was performed with immediate angiographic success, and clinical, analytical and imaging improvement in the postoperative period. Conclusion: In addition to open surgical repair and laparoscopic surgery, there are also endovascular procedures for the treatment of visceral pseudoaneurysms, so the vascular surgeon must be aware with the available strategies, taking into account the patient, the characteristics and location of the visceral pseudoaneurysm.